1988
DOI: 10.1038/jcbfm.1988.52
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Oscillations of Cortical Oxidative Metabolism in Waking and Sleep

Abstract: Summary:To study the changes in cortical oxidative me tabolism and blood volume during behavioral state tran sitions, we employed reflectance spectrophotometry of the cortical cytochrome c oxidase (cyt aa3) redox state and blood volume in unanesthetized cats implanted with bilateral cortical windows and EEG electrodes. Contin uous oscillations in the redox state and blood volume (�9/min) were observed during waking and sleep. These primarily metabolic oscillations of relatively high ampli tude were usually syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 42 publications
4
24
0
Order By: Relevance
“…They were the first to note that spontaneous fluctuations in the fMRI BOLD signal at rest in one area of the cerebral cortex exhibit systemrelevant correlations with signal fluctuations in other areas. Their initial observation, which was in somatomotor cortices, has since been replicated and extended to other brain areas (Vern et al, 1988;Biswal et al, 1997;Lowe et al, 1998Lowe et al, , 2000Lowe et al, , 2002Xiong et al, 1999;Arfanakis et al, 2000;Cordes et al, 2000Cordes et al, , 2001Cordes et al, , 2002Kiviniemi et al, 2000;Obrig et al, 2000;Hampson et al, 2002Hampson et al, , 2004Patterson et al, 2002;Peltier and Noll, 2002;Greicius et al, 2003;Peltier et al, 2003;Quigley et al, 2003;Greicius and Menon, 2004;Jiang et al, 2004;Sun et al, 2004;Van de Ven et al, 2004;Fox et al, 2005;Waites et al, 2005). These studies provided a rich new view of the intrinsic activity of the human brain characterized by spatially consistent, temporally varying activity within distinct brain systems.…”
Section: Spontaneous Fluctuations In the Bold Fmri Signalmentioning
confidence: 85%
“…They were the first to note that spontaneous fluctuations in the fMRI BOLD signal at rest in one area of the cerebral cortex exhibit systemrelevant correlations with signal fluctuations in other areas. Their initial observation, which was in somatomotor cortices, has since been replicated and extended to other brain areas (Vern et al, 1988;Biswal et al, 1997;Lowe et al, 1998Lowe et al, , 2000Lowe et al, , 2002Xiong et al, 1999;Arfanakis et al, 2000;Cordes et al, 2000Cordes et al, , 2001Cordes et al, , 2002Kiviniemi et al, 2000;Obrig et al, 2000;Hampson et al, 2002Hampson et al, , 2004Patterson et al, 2002;Peltier and Noll, 2002;Greicius et al, 2003;Peltier et al, 2003;Quigley et al, 2003;Greicius and Menon, 2004;Jiang et al, 2004;Sun et al, 2004;Van de Ven et al, 2004;Fox et al, 2005;Waites et al, 2005). These studies provided a rich new view of the intrinsic activity of the human brain characterized by spatially consistent, temporally varying activity within distinct brain systems.…”
Section: Spontaneous Fluctuations In the Bold Fmri Signalmentioning
confidence: 85%
“…We also found that BOLD changes due to neuron-astrocyte cross talk are associated with a substantial CMR O 2 response. Interestingly, periodic variations in cortical oxidative metabolism have been observed in animal studies (Vern et al 1988). This does not imply that the resting brain activity (i.e., in the absence of stimuli) is purely a vascular/metabolic effect.…”
Section: Discussionmentioning
confidence: 99%
“…38 The origin of these fluctuations and their relationship to brain neuronal activity have always been an intriguing question, but not well understood despite extensive studies. 38,39 More…”
Section: Discussionmentioning
confidence: 99%